2013
DOI: 10.1038/clpt.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Effects of Rifampicin Discontinuation on Cytochrome P450 Activity in Healthy Japanese Volunteers, Using the Cocktail Method

Abstract: Cytochrome P450 (CYP) 1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A are major factors involved in the metabolism of clinically prescribed drugs. Because the time course after drug treatment discontinuation has received little attention, we aimed to clarify the chronological changes of rifampicin-induced CYP enzyme activities after rifampicin discontinuation. Thirteen volunteers took 450 mg of rifampicin once daily, and the cocktail method, which uses caffeine, losartan, omeprazole, dextromethorphan, and midazolam as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…According to the model, the induction of the hydroxylation of BRV to BRV-OH accounts for the observed decrease in the acid BRV-AC formation. The higher induction effect of rifampin on the CYP2C19-mediated reaction over CYP2C9 is consistent with previous in vitro hepatocyte data (Raucy et al, 2002;Madan et al, 2003;Paris et al, 2009), as well as reported clinical interaction studies (Inui et al, 2013). Of interest, when tested in vitro, rifampin induces both CYP2C9 and CYP2C19 mRNA, with a somewhat larger effect on the former (Yajima et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…According to the model, the induction of the hydroxylation of BRV to BRV-OH accounts for the observed decrease in the acid BRV-AC formation. The higher induction effect of rifampin on the CYP2C19-mediated reaction over CYP2C9 is consistent with previous in vitro hepatocyte data (Raucy et al, 2002;Madan et al, 2003;Paris et al, 2009), as well as reported clinical interaction studies (Inui et al, 2013). Of interest, when tested in vitro, rifampin induces both CYP2C9 and CYP2C19 mRNA, with a somewhat larger effect on the former (Yajima et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…These results are consistent with in vivo studies using cultured human hepatocytes, where a period of 14 days was found to be sufficient for enzyme function to return to baseline levels after rifampicin removal 4. On the other hand, Inui et al reported a period of 8 days for CYP3A activity to recover after rifampicin withdrawal in healthy subjects 5. The time span required for deinduction may be variable.…”
Section: Discussionsupporting
confidence: 82%
“…Its bacterial pathogen, Mycobacterium tuberculosis (MTB), infects almost 33% of the global population, and rifampicin (RIF) is a first‐line anti‐TB drug based on its efficacy. RIF induces various cytochrome P450 (CYP) isoforms, namely 3A4, 2C9, and 2C19, which can catalyze the metabolism of drugs, including RIF. Previous research studies have indicated that low serum RIF levels are common in TB patients.…”
mentioning
confidence: 98%